Penguatan Literasi Green Economy Mahasiswa Ekonomi Syariah melalui Kunjungan Industri Bioetanol di PT Madubaru PG-PS Madukismo - Suci Yongki Setyowati; Akhmad Sirojudin Munir; Lutfi Hidayah (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
This community service activity aims to strengthen the understanding of Sharia Economics students from Universitas Sunan Drajat Lamongan regarding the green economy concept through an experiential learning approach, specifically an industrial visit to PT Madubaru PG-PS Madukismo in Yogyakarta. Seventy-eight Sharia Economics students participated in the activity, directly observing the sugarcane-based bioethanol production process as a tangible example of green industry implementation in Indonesia. The methods employed included field observations, presentations by industry practitioners, and focused discussions. Evaluation was conducted using pre-tests and post-tests to measure the improvement in participants' understanding. The activity resulted in an increase in the average pre-test score from 62.4 to 84.7 (a 35.7% rise), demonstrating a significant improvement in students' understanding of green economy and circular economy concepts, as well as the interrelationship between Sharia values ​​and environmental sustainability. This activity is expected to serve as an integrative learning model that bridges academic theory with sustainable industry practices.